Cidades médias e novas centralidades: análise dos subcentros e eixos comerciais em Uberlândia (MG) - Souza, Marcus Vinicius Mariano de (2009)
This paper aims to understand the process of decentralization of commerce and service activities in medium cities and the formation of new centralities, from analysis of sub-centers and commercial thoroughfares of the city of Uberlândia. For that, there were rescued of relations between city and trade, seeking to understand the influence of trade in the organization of urban space, which has led to propose some theories about the organization of cities by several researchers. Also were rescued the theories about the medium cities and how Uberlândia has developed, becoming an important city in the regional scenario, that, due to this, suffered changes in urban areas, like the decentralization of tertiary activities. Few are the studies in Urban Geography which were dedicated to the study of new centralities in medium cities. Thus was developed a research methodology, based on some studies that could contribute to the identification of sub-centers and commercial thoroughfares in medium cities, categories of new centralities that were analyzed in this study. It was noticed that the decentralization of tertiary activities is still in process in the city of Uberlândia, with the presence of five sub-centers and two commercial thoroughfares, which have distinct characteristics of new centralities in metropolitan areas. Furthermore, was developed a proposal for classification of sub-centers of Uberlândia, according to the methodology used. This proposal needs to be put under critiques, to serve as reference in studies on new centralities in medium cities.